IMPLEMENTING READING FOR PLEASURE AS A PEDAGOGICAL STRATEGY FOR EFL STUDENTS AT DATOKARAMA STATE ISLAMIC UNIVERSITY PALU - Afifah, Afifah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to analyze students’ pleasure in reading English and to identify reading materials, access, and habits contributing to language development. This research addresses the limited studies integrating reading pleasure, reading habits, and their impact on EFL students’ language skills. A qualitative case study design was employed involving 42 second-semester English major students at Datokarama State Islamic University Palu. Data were collected through observation and interviews and analyzed thematically. The findings reveal that digital fiction, such as online short stories, serves as the primary source of reading enjoyment, while non-fiction materials, including articles and biographies, support knowledge development. Reading access is predominantly facilitated through digital platforms such as e-books, social media, and websites. Students tend to read during leisure time, particularly in the evening. Reading pleasure contributes to vocabulary enrichment, improved pronunciation, and increased confidence in English communication. These findings highlight the importance of integrating interest-based reading strategies in enhancing students’ language competence. ABSTRAK Penelitian ini bertujuan untuk menganalisis kesenangan membaca bahasa Inggris pada mahasiswa serta mengidentifikasi jenis bacaan, akses, dan kebiasaan membaca yang berkontribusi terhadap peningkatan kemampuan bahasa. Studi ini dilatarbelakangi oleh terbatasnya kajian yang mengintegrasikan aspek kesenangan membaca dengan kebiasaan membaca dan dampaknya terhadap keterampilan bahasa pada mahasiswa EFL. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus terhadap 42 mahasiswa semester dua Program Studi Bahasa Inggris di Universitas Islam Negeri Datokarama Palu. Data dikumpulkan melalui observasi dan wawancara, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa bacaan fiksi digital seperti cerita pendek daring menjadi sumber utama kesenangan membaca, sementara bacaan nonfiksi seperti artikel dan biografi mendukung pengembangan pengetahuan. Akses membaca didominasi oleh platform digital seperti e-book, media sosial, dan situs web. Kebiasaan membaca cenderung dilakukan pada waktu senggang, terutama malam hari. Kesenangan membaca terbukti berkontribusi terhadap peningkatan kosakata, pelafalan, dan kepercayaan diri dalam berbahasa Inggris. Temuan ini menegaskan pentingnya integrasi strategi pembelajaran berbasis minat membaca dalam meningkatkan kompetensi bahasa mahasiswa.